Understanding the role of the gut microbiome in gastrointestinal cancer: A review - Duygu Ağagündüz; Ermelinda Cocozza; Özge Cemali; Ayşe Derya Bayazıt; Maria Francesca Nanì; Ida Cerqua; Floriana Morgillo; Suna Karadeniz Saygılı; Suna Karadeniz Saygılı; Roberto Berni Canani; Paola Amero; Raffaele Capasso (Frontiers Media S.A., 2023)
Gastrointestinal cancer represents one of the most diagnosed types of cancer. Cancer is a genetic and multifactorial disease, influenced by the host and environmental factors. It has been stated that 20% of cancer is caused by microorganisms such as Helicobacter pylori, hepatitis B and C virus, and human papillomavirus. In addition to these well-known microorganisms associated with cancer, it has been shown differences in the composition of the microbiota between healthy individuals and cancer patients. Some studies have suggested the existence of the selected microorganisms and their metabolites that can promote or inhibit tumorigenesis via some mechanisms. Recent findings have shown that gut microbiome and their metabolites can act as cancer promotors or inhibitors. It has been shown that gastrointestinal cancer can be caused by a dysregulation of the expression of non-coding RNA (ncRNA) through the gut microbiome. This review will summarize the latest reports regarding the relationship among gut microbiome, ncRNAs, and gastrointestinal cancer. The potential applications of diagnosing and cancer treatments will be discussed.